Preventive Detention of Immigrants and Non-Citizens in the United States since September 11th - Martin, Kate (Refuge: Canada’s Journal on Refugees, 2002)
The attacks of September 11, 2002, have dramatically altered the policy landscape in Washington, but it is important to reject the notion that there is a necessary trade-off between security and civil liberties. One of the most serious threats to civil liberties has been the adoption of a policy of preventive detention that has resulted in the secret jailing of hundreds of Arabs and Muslims when there is no evidence linking them to terrorist activity. This has been done, not by using the limited new authorities granted the government in the post-September 11 terrorism legislation, but by improperly using pre-existing criminal and immigration authorities. Secret arrests are antithetical to a democratic society. A targeted investigation that focuses on actual terrorist activity and respects the legitimate political and religious activity of citizens and non-citizens would be more effective than a dragnet approach that has resulted in the secret arrests of hundreds of individuals.